FAKTOR YANG MEMPENGARUHI PERKEMBANGAN BATITA : FAKTOR YANG MEMPENGARUHI PERKEMBANGAN BATITA - Kusumaningsih, Tri Puspa; Febriyani, Ririn (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
Research background: An important period in the development of children is toddlerhood. Basic growth and development that takes place in toddlerhood will influence and determine the next child's development. The results of a preliminary study in Kedungpoh Village found 3 toddlers who experienced growth and development disorders. Research objective: To determine the factors related to toddler development in the Working Area of ​​the Loano Health Center. Research method: Correlative research type, cross sectional approach. Sample 63 total sampling technique. Questionnaire data collection. Spearman Rank test correlation analysis technique. Research time April-May 2023. Results of the study: There is a relationship between parental stimulation (p value = 0.020), parental education (p value = 0.019), parental income (p value = 0.000), nutritional status (p value = 0.000) to toddler development. Conclusion: There is a relationship between parental stimulation, parental education, parental income, and nutritional status on toddler development. Suggestion: It is hoped that the Puskesmas can provide information through counseling and counseling to mothers who have toddlers so that they can increase their knowledge and insight about the growth and development of toddlers.